Rumen Microbiota of Tibetan Sheep (Ovis aries) Adaptation to Extremely Cold Season on the Qinghai-Tibetan Plateau - Fan, Qingshan; Cui, Xiongxiong; Wang, Zhaofeng; Chang, Shenghua; Wanapat, Metha; Yan, Tianhai; Hou, Fujiang (Frontiers in Veterinary Science, 2021)
The Qinghai-Tibet Plateau is characterized by low temperatures and hypoxia, and this feature is more obvious in the winter. However, it is not clear how Tibetan sheep adapt to extreme cold climates. To address this, we used physiological methods combined with next-generation sequencing technology to explore the differences in growth performance, nutrient digestibility of forage, serum biochemical index, and rumen microbial community of Tibetan sheep (Ovis aries) in the summer and winter. In the summer, owing to the high nutritional quality of the forage, the Tibetan sheep showed high values of forage degradation and fermentation, associated with high counts of important bacteria in the rumen, such as Prevotella_1, Bacteroidetes, Prevotellaceae_UCG-003, Ruminococcus_1, Saccharofermentans, and Ruminococcaceae_UCG-014. These bacteria were also associated with an improved growth performance and increased serum immunity and antioxidant status. In the winter, owing to the low nutritional quality of the forage, the Tibetan sheep presented low values of forage degradation and fermentation. The relative abundance of Firmicutes and Firmicutes/Bacteroidetes, microbial diversity, cooperation between microorganisms, and metabolism were significantly increased, implying that the rumen microbiota could promote the decomposition of forage biomass and the maintenance of energy when forage nutrition value was insufficient in the winter. Our study helps elucidating the mechanism by which Tibetan sheep adapt to the high-altitude harsh environment, from the perspective of the rumen microbiota.